Works Linking in The Context of Cultural Security - Marta Pomykała (Communications of International Proceedings, 2021)
Cultural security is defined as the state's ability to protect its cultural identity, cultural goods and national heritage, under conditions of openness to the world, allowing culture to flourish through the internalisation of values incompatible with its own identity. The purity of language, cultural heritage, customs and religion, which make up the cultural identity of a given society, remain under exceptional protection here. The protection of cultural heritage is currently taking on a new dimension, especially in view of the widespread use of modern information technologies, including the opportunities afforded by communication via the Internet. Intellectual property is an area that requires special protection in this context, and one of the basic legal problems in this respect is the question of proper and lawful making available of works in the digital environment. The aim of this publication is to discuss legal linking and linking in the light of the legislation and case law of the European Court of Justice. For this purpose the method of dogmatic-legal analysis and comparative analysis has been used. Conclusions, on the other hand, may serve as a basis for the improvement of state law.
Keywords: Linking Works; Internet; Cultural Identity; Cultural Security.